Decreased Steroid Hormone Receptor NR4A2 Expression in Kawasaki Disease Before IVIG Treatment - Huang, Ying-Hsien; Chen, Kuang-Den; Lo, Mao-Hung; Cai, Xin-Yuan; Kuo, Ho-Chang (Frontiers in Pediatrics, 2019)
Kawasaki disease (KD) is anacute febrile coronary vasculitis disease in children. In general, this disease can be treated with a single dose of 2 g/kg intravenous immunoglobulin (IVIG). However, the best timing for administering steroid treatment in acute-stage KD is still under debate. In this study, we recruited 174 participants to survey the transcript levels of steroid hormone receptors in KD patients. The chip studies consisted of 18 KD patients that were analyzed before IVIG treatment and at least 3 weeks after IVIG administration, as well as 36 control subjects, using GeneChip® HTA 2.0. Another cohort consisting of 120 subjects was analyzed to validate qRT-PCR. Our microarray study demonstrated significant downregulated expressions of the mRNA levels of NR1A2, RORA, NR4A1-3, THRA, and PPARD in KD patients in comparision to the controls. However, these genes increased considerably in KD patients after IVIG administration. After PCR validation, our data only revealed decreased NR4A2 mRNA expression in the KD patients compared to those of the controls, which increased after they received IVIG treatment. Our study is the first to report the potential effective utilization of steroid treatment in KD. Prior to IVIG treatment, decreased steroid receptors allowed for the reduced treatment role of steroids. However, after IVIG treatment, increased steroid receptors indicate that steroids are effective as a supplementary treatment for KD.